Nucleosomal arrangement affects single-molecule transcription dynamics - Fitz, Veronika; Shin, Jaeoh; Ehrlich, Christoph; Farnung, Lucas; Cramer, Patrick; Zaburdaev, Vasily; Grill, Stephan W. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
In eukaryotes, gene expression depends on chromatin organization. However, how chromatin affects the transcription dynamics of individual RNA polymerases has remained elusive. Here, we use dual trap optical tweezers to study single yeast RNA polymerase II (Pol II) molecules transcribing along a DNA template with two nucleosomes. The slowdown and the changes in pausing behavior within the nucleosomal region allow us to determine a drift coefficient,., which characterizes the ability of the enzyme to recover from a nucleosomal backtrack. Notably, chi can be used to predict the probability to pass the first nucleosome. Importantly, the presence of a second nucleosome changes chi in a manner that depends on the spacing between the two nucleosomes, as well as on their rotational arrangement on the helical DNA molecule. Our results indicate that the ability of Pol II to pass the first nucleosome is increased when the next nucleosome is turned away from the first one to face the opposite side of the DNA template. These findings help to rationalize how chromatin arrangement affects Pol II transcription dynamics.
Keywords: Pol II; transcription; single-molecule; optical tweezers; internucleosomal distance